2022
DOI: 10.1177/08850666221113252
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin as a Predictor of Outcomes in Hospitalized Patients with Covid-19 Pneumonia

Abstract: Purpose: Elevated ferritin levels are associated with poor outcomes in Covid-19 patients. Optimal timing of ferritin assessment and the merit of longitudinal values remains unclear. Methods: Patients admitted to Henry Ford Hospital with confirmed SARS-CoV-2 were studied. Regression models were used to determine the relation between ferritin and mortality, need for mechanical ventilation, ICU admission, and days on the ventilator. Results: 2265 patients were evaluated. Patients with an initial ferritin of > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…The current study considered ferritin as a predictor of ICU admission. This result was in concordance with the findings of Shakaroun et al 52 Oxidative imbalance in COVID-19 patients can be determined by measuring oxidative stress biomarkers such as MDA and antioxidant biomarkers. Our study shows a higher level of MDA in the critical group than in HCs, this is consonance with the published work by Avila-Nava et al, 25 Mehri et al 53 The reason for increasing MDA may be due to high levels of free radicals in COVID-19 that accelerate the rate of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
“…The current study considered ferritin as a predictor of ICU admission. This result was in concordance with the findings of Shakaroun et al 52 Oxidative imbalance in COVID-19 patients can be determined by measuring oxidative stress biomarkers such as MDA and antioxidant biomarkers. Our study shows a higher level of MDA in the critical group than in HCs, this is consonance with the published work by Avila-Nava et al, 25 Mehri et al 53 The reason for increasing MDA may be due to high levels of free radicals in COVID-19 that accelerate the rate of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
“…Strong correlations between obesity in adolescents and elevated ferritin levels were also described [ 24 ]. Interestingly, in the course of COVID-19, high ferritin levels correlated with a more frequent occurrence of cytokine storm in patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin level is raised in infectious and inflammatory diseases (Kernan & Carcillo, 2017). Among the inflammatory biomarkers, serum ferritin has the ability to define the disease course of COVID‐19 and predict the need for ICU admission and mortality (Kaushal et al, 2022; Shakaroun et al, 2022). Though our study observed a higher ferritin level in non‐survivor patients, it did not prove it as a significant risk factor of ICU admission or mortality when adjusted for other factors.…”
Section: Discussionmentioning
confidence: 99%